PREPARATION AND EVALUATION OF HERBAL ANTI-ACNE GEL - K.YAMINI; T.ONESIMUS (International Journal of Pharma and Bio Sciences, 2013)
Herbal formulations have growing demand in the world market. The present work deals with the development and evaluation of the herbal Anti-Acne gel containing hydro-alcoholic extract of Neem leaves (Azadirachta indica) and the fruits of Nutmeg (Myristica fragrance). The plants have been reported in the literature having good anti-microbial, anti-oxidant and anti-inflammatory activity. Various formulation batches i.e., F1 to F15 were prepared and evaluated for various parameters like colour, appearance, consistency, washability, pH, spreadability and antimicrobial activity.. Optimized formulation was compared with the marketed preparation. Amongst all the formulation studied batch F4 was found optimum for all the parameters. It is a very good attempt to establish the herbal gel containing hydro-alcoholic extract of neem leaves (Azadirachta indica) and fruits of nutmeg (Myristica fragrance).